Effectiveness of augmented reality warnings on driving behaviour whilst approaching pedestrian crossings: A driving simulator study. (November 2020) - Calvi, Alessandro; D'Amico, Fabrizio; Ferrante, Chiara; Bianchini Ciampoli, Luca
Highlights: Data crashes show that more than 280, 000 victims of road crashes are pedestrians. The majority of road crashes are caused by poor driver oversight of road users. Augmented Reality technology could enable future systems to detect dangers earlier. Several AR video and audio warnings are tested in a driving simulator study. AR effectiveness in improving the safety of pedestrian crossings is demonstrated. Abstract: In this paper, the potential of using Augmented Reality (AR) technology to improve the safety of pedestrian crossings was tested, by means of virtual information provided to a driver approaching a zebra crossing area. To achieve this objective, a driving simulator study was carried out. The effectiveness of the system was tested, and the results of the developed simulation tests, with and without AR warning to inform the driver of a pedestrian crossing ahead, were compared. Specifically, AR warnings were tested under two different situations: a visible pedestrian crossing the roadway and a non-visible pedestrian, made invisible by certain obstacles, and who is about to cross the roadway. Two different virtual warnings were tested - in both cases - on a sample of forty-six participants: a flashing red arrow above the pedestrian, and the same visual warning but with an additional audible warning system. The effects of the audible warnings were studied by comparing the driving performances (decelerations, speeds and distances) and surrogate safety measures (Time-to-Collision (TTC) and Time-to-Zebra (TTZ)) with those recorded under reference conditions (without the audible warnings). Positive effects of AR were observed. Specifically, when the AR warnings were activated, drivers started to decelerate well before the pedestrian crossing, with a low deceleration rate and high TTC and TTZ. This study confirmed the great benefits that AR and connected vehicle technologies could bring to the overall safety conditions on the road network, especially under risky situations and difficult maneuvers. The driving simulator is certainly an effective solution for studying and evaluating such technologies, as well as studying their impact on driving performance.